In vitro endophyte-host plant interaction study to hypothetically describe endophyte survival and antifungal activities in planta - Yo, Hye Seung; Su Yien Ting, Adeline (Acta Biologica Szegediensis, 2017)
This study is the first to adopt a hypothetical approach to establish the influence of the complex endophyte-host interaction on endophyte survival and antifungal expression. Three k interactions were evaluated; (I) influence of host-induced enzymes on endophyte growth (biomass) and colonization, (II) link between endophyte-produced cellulase, their growth and colonization, and (III) the influence of host environment on antifungal expression of endophytes. The interactions with the host were performed using plant slurry (PS) to mimic in planta (host) environment with analysis on interactions evaluated using Pearson correlation coefficients (r). Results revealed that host induced enzymes may be a limiting factor to colonization of endophytes with inverse correlations observed (-0.046 ≤ r ≤-0.7164). These enzymes may also limit growth of endophyte although, PAL (r = 0.536) and TPC (r = 0.8894) appeared contrary. Results were also suggestive that endophytes produced cellulase to aid in colonization in host plants (r = 0.7073 in PS), and cellulase activities are continuously produced even when growth of endophytes are limited (r = -0.314 in PS). Endophytes are presumed to produce antifungal compounds in planta (r = 0.2760 in PS), and these compounds may be secondary metabolites, which are primarily produced under nutrient-depleted conditions where growth is poor (in host plant). The superior growth of endophytes in synthetic PDB media has an inverse correlation to antifungal activity (r = -0.5129), confirming that secondary metabolites are involved in antifungal activities. This study clearly presents that success of inoculated endophytes in colonizing, growing and expressing antifungal activities is dependent on the host plant.